Edge of battle Mcnab's got serious company - Brown, Dale (London HarperCollins publishers, 2006)
Jason Richter and his high-tech unit Task Force TALON are charged with securing the Mexican border, where a terrorist band has been operating with impunity and enflaming the passions of the population.